MANAJEMEN KOPERASI TERPADU DALAM PENDIDIKAN KEWIRAUSAHAAN DI USAHA KECIL DAN MENENGAH - Herdi; Sri Murningsih; Triyono Widodo; Siti Mariah; Meity Suryandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Entrepreneurship education has become a crucial element in economic development, particularly in driving the growth of small and medium-sized enterprises (SMEs). Despite their critical role, many SMEs face challenges in managing and developing their businesses. Cooperatives, as institutions based on solidarity and mutual cooperation, offer a solution through an integrated cooperative management model that supports entrepreneurship education. This research employs a library research method to explore the effectiveness of this management model in enhancing entrepreneurial capacity in SMEs. The findings reveal that the integrated cooperative management model significantly contributes to improving the competitiveness and sustainability of SMEs, though its success is highly dependent on the managerial competence within the cooperative and support from various stakeholders. Keywords: Integrated Cooperative Management, Entrepreneurship Education, Small and Medium Enterprises;